Risk of exposure to acrylamide - Bušová, Milena; Bencko, Vladimír; Veszelits Laktičová, Katarína; Holcátová, Ivana; Vargová, Mária (Central European Journal of Public Health, 2020)
OBJECTIVES: Acrylamide is a toxic compound that can be found it both occupational and non-occupational environments. This study focuses on its sources and health effects of its exposure. METHODS: Adverse effects of acrylamide, especially carcinogenic, genotoxic, and teratogenic were reported in many studies conducted on animals. Neurotoxicity was reported in workers exposed to acrylamide in the occupational environment. Another important source of populations' exposure to acrylamide is their nutrition. RESULTS: This study focuses on humans' exposure to acrylamide from various sources and its harmful effects on their health. CONCLUSIONS: Dietary intake of acrylamide, as well as occupational exposure, cigarette smoking, cosmetics usage and other environmental sources could have a significant effect on human health.
Keywords: Animals; nutriční stav; DNA Damage; Nutritional Status; lidé; Occupational Exposure; zvířata; poškození DNA; pracovní expozice; karcinogeny; Carcinogens; Acrylamide; akrylamid; Humans